The elastic and ductile behaviour of CLT wall-floor connections and the influence of fastener length. (15th June 2019) - O'Ceallaigh, Conan; Harte, Annette M.
Highlights: The failure behaviour of wall-floor connections in C16 CLT has been examined. Connection strength increases with increasing fastener length. Connection ductility generally decreased with increasing fastener length. EC5 analytical connection stiffness is non-conservative for C16 CLT. Recommendations for overstrength and strength degradation factors are presented. Abstract: An investigation was carried out to examine the influence of the fastener length on the elastic and ductile failure behaviour of typical steel-to-timber bracket connections in Cross Laminated Timber (CLT) manufactured from C16 spruce. The behaviour of single screw-type fasteners within CLT of length 25 mm, 50 mm and 75 mm are examined under tension and shear loading. Multiple screw-type fasteners have been utilised to examine monotonic and cyclic behaviour of steel bracket-fastened CLT connections under shear and tension loading. Characteristic values of the experimental results are compared to analytical models from current timber design codes and the literature. The length of fastener has been shown to influence the failure strength and ductility of the connection. The overstrength factors and strength degradation factors have been shown to be similar, regardless of fastener length, and conservative values are recommended.